SHIFT IN NEW PROGRAMMING LANGUAGE PARADIGMS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article explores the current trends in programming language development and paradigm-level shifts. Functional, reactive, declarative, and AI-oriented paradigms are increasingly replacing traditional imperative and object-oriented approaches. The study investigates the reasons behind these developments, their areas of application, and efficiency indicators. Through practical analysis, the differences between paradigms are highlighted, and conclusions are drawn regarding which paradigms are likely to dominate the future of software development.